2021
DOI: 10.3389/fnut.2021.700936
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Eating Speed and Metabolic Syndrome: A Systematic Review and Meta-Analysis

Abstract: Objective: This review aimed to systematically summarize and meta-analyze the association between eating speed and metabolic syndrome (MetS).Methods: Following the Preferred Reporting Items for Systematic Reviews, and Meta Analyses (PRISMA) guidelines, four electronic databases (PubMed, Web of Science, MEDLINE, and EMBASE) were searched until March 2021 to identify eligible articles based on a series of inclusion and exclusion criteria. Heterogeneity was examined using I2 statistics. Using random-effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…In addition, we found a dose-response association between eating faster and higher BMI, which is consistent with the results of previous studies. 4,9,27 This study suggested that the regions with the significantly largest positive associations with SBP and DBP, with or without adjustment for BMI, showed overnutrition and higher salt intake. The positive association between salt intake and blood pressure is well known, 10,25 which was consistent with our finding.…”
Section: Lifestyle-related Risk Factors For Bmi and Blood Pressurementioning
confidence: 67%
See 1 more Smart Citation
“…In addition, we found a dose-response association between eating faster and higher BMI, which is consistent with the results of previous studies. 4,9,27 This study suggested that the regions with the significantly largest positive associations with SBP and DBP, with or without adjustment for BMI, showed overnutrition and higher salt intake. The positive association between salt intake and blood pressure is well known, 10,25 which was consistent with our finding.…”
Section: Lifestyle-related Risk Factors For Bmi and Blood Pressurementioning
confidence: 67%
“…Through observational and intervention studies, evidence of the relationship between lifestyle-related factors and BMI or BP, such as the association between smoking cessation and increased BMI, exercise and decreased BP, faster eating and increased BMI, and alcohol consumption and increased BP, has been accumulated. 2-10 However, these studies have mainly focused on the association between single lifestyle-related risk factors and outcomes, with few studies examining the comprehensive association between multiple lifestyle-related risk factors and the outcomes. In Japan, annual health checkups screen for metabolic syndrome or pre-metabolic syndrome, and evidence-based national health guidance is provided to those at risk.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we defined the criterion controlling important confounding factors: maternal age at menarche, maternal education level, household income, weight, and height. Referring to the previous meta-analysis [ 19 ], the studies were deemed to be low, moderate, and high quality according to the score “0–3”, “4–6”, and “7–9”, respectively. The Agency for Healthcare Research and Quality (AHRQ) scale was used to assess cross-sectional studies.…”
Section: Methodsmentioning
confidence: 99%
“…10 A meta-analysis of the crosssectional and longitudinal association between eating speed and metabolic outcomes showed that faster eating rate is associated with higher risks for the metabolic syndrome, central obesity, elevated blood pressure and increased fasting plasma glucose compared with slower eating. 11 Brain regions in relationship to food cues Although the underlying cause(s) of food cravings are not deeply understood, it has been shown in the general, non-pregnant population that cue-induced cravings in response to food pictures predict disordered eating and excess weight gain. In a meta-analytical review of 45 studies, exposure to food stimuli (pictures) and the experience of craving influence eating behaviour and further weight gain independently of baseline body mass index (BMI), age and gender.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Studies showed that faster eating rate is associated with increased food intake9 and an increased risk of obesity 10. A meta-analysis of the cross-sectional and longitudinal association between eating speed and metabolic outcomes showed that faster eating rate is associated with higher risks for the metabolic syndrome, central obesity, elevated blood pressure and increased fasting plasma glucose compared with slower eating 11…”
Section: Introductionmentioning
confidence: 99%